Effect of Moderate Versus High Intensity Interval Exercise Training on Vascular Function in Inactive Latin-American Adults: A Randomized Clinical Trial - Garcia-Hermoso, A (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Sin Resumen Disponible